2017
DOI: 10.17014/ijog.4.3.193-208
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic Analysis in Determining Tectonic Activity Affected by Sumatra Fault in Liwa Region and Its Surrounding Area, Lampung, Indonesia

Abstract: -The study discusses about characteristics of Sumatra Fault and its tectonic activity in Liwa and the adjacent area. The research uses quantitative methods of verification hypothetical deduction, which starts from the general approach, then it pursues into more specialized and focused ones. While the research work includes field measurements, remote sensing with GIS, and geomorphologic analysis using morphometry, such as: sinousity of mountain front (Smf), percentage of facets, ratio of the width and height of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Goudie (2004) stated that sinuosity mountain front was an index reflecting the balance between erosional forces that tend to cut embayment into a mountain front and the tectonic forces that tended to produce a straight front coincident with an activity range-boundary fault. In addition, Yudhicara et al (2017) stated that the intensive uplift was indicated by a low S mf value. Given mountain fronts which associate with active tectonics are straight; they have low values of S mf .…”
Section: Valley Floor Width To Valley Height Ratio (V F )mentioning
confidence: 99%
“…Goudie (2004) stated that sinuosity mountain front was an index reflecting the balance between erosional forces that tend to cut embayment into a mountain front and the tectonic forces that tended to produce a straight front coincident with an activity range-boundary fault. In addition, Yudhicara et al (2017) stated that the intensive uplift was indicated by a low S mf value. Given mountain fronts which associate with active tectonics are straight; they have low values of S mf .…”
Section: Valley Floor Width To Valley Height Ratio (V F )mentioning
confidence: 99%
“…From geomorphological perspective, the research area is classified as part of the Barisan Mountains, characterized by the morphology of wavy hills and lowlands, which are influenced by tectonic activity (Mangga et al, 1993;Yudhicara et al, 2017;Radityo et al, 2020). Based on the Regional Geological Map of Tanjungkarang (Mangga et al, 1993), the research area consists of several rock formation units, namely Tarahan Formation (Tpot), Lampung Formation (QTl), and Betung Young Volcanic Deposit (Qhv (b)) which are dominated by Tertiary to Quaternary volcanic products.…”
Section: Introductionmentioning
confidence: 99%
“…Landscape and spatial data are very important for studying active tectonics because they can estimate the exact position and historical seismic records (Arrowsmith & Zielke, 2009). Tectonic geomorphological analysis has been widely used as a parameter to measure earthquake hazard in an area (Galadini and Galli, 2000;Faghih et al, 2015;Keller and Pinter, 1996;El Hamdouni et al, 2008;Yudhicara et al, 2017;Hidayat, 2010). Large landforms of the Earth's surface resulting from the competition between uplift and denudation processes were studied (Burbank and Anderson, 2001).…”
Section: Introductionmentioning
confidence: 99%